The Impact of Using Disk Media (Smart Wheel Game) On Mother’s Knowledge About Adverse Events Following Immunization (AEFI) in Infant’s Basic Immunization - Kamalah, Rizqi; Pajala, Rosmini; Harlinah, Harlinah (Journal Midwifery Jurusan Kebidanan Politeknik Kesehatan Gorontalo, 2024)
Child immunization is an effort to obtain immunity artificially body parts of germs to form antibodies. In West Papua from January to July 2021, there are 63% of children aged 0-11 months who do not or have incomplete immunization status. One of the causal factors, that mothers are worried about the effects of post-immunization, so mothers are reluctant to take children to get immunizations for that the officers anticipate by providing counseling using disc media with an explanation of the effects of immunization that may occur and how they are handled. The purpose of this study was to determine the effect of disc media on mother’s knowledge about adverse events following immunization, AEFI (or in Indonesian we called KIPI) basic immunization in infants at Segun Health Center, Sorong Regency. This study used a quasi-experimental design with posttest only control group design, with two groups randomly selected. The population in this study used infant with a total of 32 respondents. The results of the statistical test using chi square test were obtained p-value = 0.017 (p-value≤0.05) which means there is an influence towards positive way of disc media administration on the mother's knowledge of the adverse event following immunization in infants at the Segun Health Center, Sorong Regency.